Symposium 2: Challenges to social justice and collective wellbeing in a globalised education system: Symposium Introduction - Beetham, Helen; Czerniewicz, Laura; Jones, Chris; Lally, Victor; Perotta, Carlo; Sclater, Madeleine (Proceedings of the International Conference on Networked Learning, 2016)
Access to educational opportunity is undoubtedly extended by the availability of open learning materials, networked learning communities, and forms of open accreditation. Networked learning has, in that sense, fulfilled many of the promises of its early pioneers. The evidence is weak, however, that access to digital opportunity translates into educational success for those without other forms of educational, social and cultural capital. The distribution of functional access to digital opportunity in fact mirrors other kinds of inequality very closely, so the proliferation of networked learning opportunities can actually amplify inequalities of outcome. Beyond individual cases, an open digital landscape for learning favours globally successful institutions, as shown by the scramble to form ‘gold standard’ open course networks among leading universities. A global market in educational content risks amplifying the hegemony of the languages, educational cultures and knowledge practices of the English-speaking global north. A parallel global market in the most able and motivated students puts further pressure on the local education systems that are most able to support those currently disadvantaged. This symposium examines the globalised educational landscape from a radical, critical perspective. Some of us write from within schools of education with the experience of research and publishing behind us. From this perspective we assert the value of theory-informed research to highlight the contradictions, the political negotiations and the vulnerabilities of hegemonic discourses, to encourage scepticism and to challenge determinist views of our technological future. Some of us write from situations of responsibility in practice and policy settings. From this perspetive we assert that there are no technological solutions to inequality, only political and emancipatory educational actions. What tools of resistance are at our disposal within the academic labour force and in the ’world of work’ adjacent to it? Our discussions and the links among our papers represent the hope that the divide can sometimes be bridged, and that theory-based interventions in education are always possible, on the side of social justice and collective wellbeing.